Association of Albumin–Bilirubin (ALBI) Grade With 28-Day All-Cause Mortality in Patients With Acute Respiratory Distress Syndrome: A Retrospective Analysis of the MIMIC-IV Database - Weixiao Chen; Qingzhou Chen; Zhiwei Tang; Zhibo Li; Weiyan Chen; Xuming Xiong; Deliang Wen; Zhenhui Zhang (Mediators of Inflammation)
The albumin–bilirubin (ALBI) grade, a validated prognostic tool in cancers such as hepatocellular carcinoma, has not been evaluated in acute respiratory distress syndrome (ARDS). This retrospective cohort study, utilizing data from the MIMIC-IV (v3.0) database, aimed to assess ALBI’s predictive value for 28-day all-cause mortality in 338 adult ARDS patients admitted to the ICU. Patients were stratified into survivors (209 cases) and nonsurvivors (129 cases), with a 28-day mortality rate of 38.2%. Multivariable Cox regression identified ALBI as an independent predictor of 28-day mortality (HR = 1.46, 95% CI: 1.09–1.95, p=0.011). Receiver operating characteristic (ROC) analysis yielded an area under the curve (AUC) of 61.1% (95% CI: 54.7%–67.4%) with an optimal ALBI cutoff of −1.681; Kaplan–Meier (KM) survival curves confirmed significantly higher mortality in patients with ALBI ≥−1.681 versus ALBI <−1.681 (p=0.0098). Subgroup analyses revealed no significant interactions between ALBI and clinical variables (interaction p: 0.672–0.85). These findings demonstrate ALBI’s utility as a novel, independent prognostic marker for short-term mortality risk in ARDS patients.